Feminism in Poetry During the Abbasid Era: The Representation of Women in the Poem Quluubu An-Nisaai Sakhurun by Abbas bin Ahnaf - Muslimah, Anisa Siti; Muhlisin, Mumu; Wiwaha, Rizzaldy Satria; Mostafa, Mohamed Abd El Motaleb; Rusmana, Dadan (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study aims to analyze feminist values in literature during the Abbasid era, particularly in the representation of women in the poem "Quluubu An-Nisaai Sakhurun" by Abbas bin Ahnaf. The research employs a descriptive qualitative method with data collection techniques that include literature reviews and analysis of relevant documents. The study identifies that feminism in this work is evident through the depiction of women as objects of admiration while simultaneously portraying them as complex characters. Social and cultural factors, such as patriarchy, shape how women are represented in this poem, reflecting the norms prevailing during that period. This study contributes by highlighting the relevance of feminist perspectives in understanding classical literature and providing insights into the relationship between social structures and literary creation.